Evaluation of oral health-related quality of life in burn survivors: A cross-sectional study - Hetal Amipara; Rakesh Kain; Shalabh Kumar (Indian Journal of Burns)
Purpose: The face, crucial to identity, is susceptible to the functional and psychological impact of burn injuries. Limited literature exists on the specific link between facial burns and oral health-related quality of life (OHRQoL). This study aims to fill this gap by investigating factors associated with OHRQoL in patients with facial burn injuries, using the validated Oral Health Impact Profile (OHIP-14) questionnaire. Materials and Methods: A cross-sectional observational study was conducted on individuals with facial burns. Participants underwent a facial examination, oral screening, and self-administered OHIP-14 questionnaires. The primary aim was to evaluate the OHRQoL in patients with facial burns. Secondary outcome variables aimed to assess the connections between the prevalence and severity of impact and oral hygiene status. Results: The study included 100 patients with facial burns, comprising 69% males and 31% females. The mean OHIP-14 severity score was 30.6 ± 10.62, significantly higher in females (P = 0.0001*). Caries prevalence was 51%, and periodontal disease prevalence was 100%. Individuals with facial burns impacting the angle of mouth had a mean mouth opening of 19.87 ± 9.48 mm, notably less than those without angle involvement, with a mean of 36.37 ± 6.10 mm (P = 0.0001*). Pearson’s correlation coefficient and independent samples t-test were used to depict the comparison of parameters. Conclusion: Burn injuries have profound and enduring impacts on physical, psychological, and oral health. Maintaining optimal oral hygiene is crucial for minimizing complications and promoting the overall well-being of individuals recovering from facial burns.